Productivity and reproductive performance of the free range local domestic fowl ecotypes in Tanzania - Msoffe, P.L.M.; Mtambo, M.M.A.; Minga, U.M.; Olsen, J.E.; Juul-Madsen, H.R.; Gwakisa, P.S.; Mutayoba, S.K.; Katule, A.M. (CIPAV, 2004)
A study was conducted to assess the productivity and reproductive performance of seven free-range local domestic fowl ecotypes in Tanzania named Ching'wekwe, Mbeya, Morogoro-medium, N'zenzegere, Pemba, Tanga and Unguja. Average weekly weight measurements and growth rates were evaluated for each ecotype and sex as was egg weight, fertility and hatchability. Significant differences existed between ecotypes in all the five parameters studied. Ching'wekwe showed consistently low mean weekly weights, daily growth rate and mean egg weight contrary to Morogoro-medium and Tanga ecotypes. Egg fertility was low with only N'zenzegere and Unguja ecotypes exceeding 75%. Hatchability was also low ranging from 55% (Ching'wekwe and Morogoro-medium) to 74% (Pemba). It was concluded that genetic and phenotypic diversity exists in the local domestic fowl ecotypes of Tanzania. The diversity constitutes a valuable resource for use in breeding programmes for improvement of the health and productivity of the local domestic fowls and in designing proper conservation strategies. Further studies are required to identify genetic markers associated with productivity and disease resistance within the local domestic fowl ecotypes. In depth studies on the performance of the Tanzanian medium ecotypes (Morogoro-medium and Tanga) is required to ascertain their suitability for promotion throughout the country.